Public Lecture on Reducing the Risk of Hearing Loss in the Elderly in Surabaya City's Wonokromo Subdistrict - Roesbiantoro, Andi; Budhi Setianto; Adriansyah, Agus Aan; Karmila, Hartatiek Nila; Afina, Rizka Dany; Sa'adah, Nikmatus (Journal of Health Community Service, 2025)
The sensorineural hearing loss experienced by the elderly is known as presbycusis. Generally, sensorineural hearing loss is permanent. The prevalence of hearing loss in Indonesia, according to 2013 Rikesdas data, is 2.6%. According to the elderly population in the age range of 65-85 years who experience hearing loss is as much as 30%. The highest rate of hearing loss was found in the age group ≥75 years, namely 36.6%. This community service aims to increase knowledge related to preventing hearing risks in the elderly in RW 07, Wonokromo Village, Surabaya City. Counselling, by carrying out outreach activities by holding a Lay Seminar in the Context of Preventing the Risk of Hearing Loss for the Elderly in RW 7, Wonokromo sub-district, Surabaya City. This lay seminar was very beneficial for the seminar participants. Characteristics of the seminar participants were that most of them were women with the most education, 49 years old, aged > 60 years and working as retirees, the results of the pretest and post-test showed an increase of 19.3% from the test statistically there a significant difference between the Pretest and Post Test